How Should Norway Respond to Ageing? - Antolín, Pablo (OECD Economics Department Working Papers, 2001)
Norway, like most OECD countries, will experience a significant ageing of its population, although it will be less dramatic. Moreover, it starts from an enviable position: employment rates of older people are among the highest in the OECD, pension outlays are currently relatively low and substantial financial assets have been accumulated in the Government Petroleum Fund. However, without reforms, due to the maturing of the pension system, ageing will lead to one of the biggest increases in pension spending as a share of GDP in OECD countries over the next 50 years. This paper thus, after exploring the scale of the demographic changes, examines the relevant institutions and their effect on the decision to retire. In light of the expected increase in the elderly, various issues concerning their economic position and health care are considered. The paper then presents the fiscal impact of ageing: the cost of the pension system will more than double, while health care spending for the ...